Assessing the impacts of Best Management Practices on nitrate pollution in an agricultural dominated lowland catchment considering environmental protection versus economic development. (1st July 2017) - Haas, Marcelo B.; Guse, Björn; Fohrer, Nicola
Abstract: Water quality is strongly affected by nitrate inputs in agricultural catchments. Best Management Practices (BMPs) are alternative practices aiming to mitigate the impacts derived from agricultural activities and to improve water quality. Management activities are influenced by different governmental policies like the Water Framework Directive (WFD) and the Renewable Energy Sources Act (EEG). Their distinct goals can be contrasting and hamper an integrated sustainable development. Both need to be addressed in the actual conjuncture in rural areas. Ecohydrological models like the SWAT model are important tools for land cover and land use changes investigation and the assessment of BMPs implementation effects on water quality. Thus, in this study, buffer strip, fertilization reduction and alternative crops were considered as BMPs and were implemented in the SWAT model for the Treene catchment. Their efficiency in terms of nitrate loads reduction related to implementation costs at the catchment scale was investigated. The practices correspond to the catchment conditions and are based on small and mid areal changes. Furthermore, the BMPs were evaluated from the perspective of ecologic and economic policies. The results evidenced different responses of the BMPs. The critical periods in winter were addressed by most of the BMPs. However, some practices like pasture land increase need to be implemented in greater area for better results in comparison to current activities. Furthermore, there is a greater nitrate reduction potential by combining BMPs containing fertilization reduction, buffer strips and soil coverage in winter. The discussion about efficiency showed the complexity of costs stipulation and the relation with arable land and yield losses. Furthermore, as the government policies can be divergent an integrated approach considering all the involved actors is important and seeks a sustainable development. Highlights: Nitrate loads are well reproduced with an eco-hydrological catchment model. Reduction of nitrate loads varies for different Best Management Practices (BMPs). Combinations of different BMPs are most effective in nitrate loads reduction. Evaluation of BMPs efficiency in context of nitrate loads reduction and yield loss. Complex conciliation of distinct governmental policies and sustainable development.